2021
DOI: 10.3389/fcell.2021.620883
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide Treatment Induces HMGB1 to Promote the Formation of Glioma Stem Cells via the TLR2/NEAT1/Wnt Pathway in Glioblastoma

Abstract: Formation of glioma stem cells (GSCs) is considered as one of the main reasons of temozolomide (TMZ) resistance in glioma patients. Recent studies have shown that tumor microenvironment-derived signals could promote GSCs formation. But the critical molecule and underlying mechanism for GSCs formation after TMZ treatment is not entirely identified. Our study showed that TMZ treatment promoted GSCs formation by glioma cells; TMZ treatment of biopsy-derived glioblastoma multiforme cells upregulated HMGB1; HMGB1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…Multiple studies reported increased expression and an oncogenic effect for NEAT1 in glioma (147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160). NEAT1 increased the activity of several signaling pathways with key roles in the cell cycle, including WNT/b-Catenin and mTOR signaling, leading to increased proliferation, invasion, and metastasis and decreased apoptosis.…”
Section: Role In Tumor Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies reported increased expression and an oncogenic effect for NEAT1 in glioma (147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160). NEAT1 increased the activity of several signaling pathways with key roles in the cell cycle, including WNT/b-Catenin and mTOR signaling, leading to increased proliferation, invasion, and metastasis and decreased apoptosis.…”
Section: Role In Tumor Pathologymentioning
confidence: 99%
“…Determining treatment response : lncRNAs modulate treatment response by affecting sensitivity to chemotherapy drugs, mainly TMZ or cisplatin, or altering radiosensitivity. Higher NEAT1 ( 151 , 160 ), XIST ( 172 ), FOXD2-AS1 ( 189 , 192 ), TP73-AS1 ( 251 ), CCAT2 ( 252 ), and lncSBF2-AS1 ( 241 ) were associated with TMZ-resistance. These effects are mediated via several mechanisms.…”
Section: Lncrnas In Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…It was later found that miR-370-3p is downregulated in GBM, which contributes to the increased expression of NEAT1 by reducing its inhibition [105]. The effect of NEAT1 on β-catenin activity also contributes to therapeutic resistance-TMZ induces the expression of the HMGB1 protein, which, via TLR2, increases NEAT1 expression [106]. The HOTAIRM1 lncRNA is expressed within the HOXA gene cluster and promotes DNA looping by scaffolding with the HOXA9 gene to form a topologically associated domain.…”
Section: Lncrna Expression Deregulationmentioning
confidence: 99%
“…However, more than 50% of glioma patients received TMZ treatment show resistance to TMZ therapy ( Lee, 2016 ). This is attributed to GSCs recalcitrance to TMZ therapy due to their enhanced DNA repair ability or/and high methyl guanine methyl transferase expression ( Hu et al, 2019 ; Gao et al, 2021 ). Small molecule compounds, including clofoctol ( Hu et al, 2019 ), LLP-3 ( Guvenc et al, 2013 ), gboxin ( Shi Y. F. et al, 2019 ), inhibitor of dopamine receptor D4 ( Dolma et al, 2016 ), and inhibitor of STAT3 ( Shi et al, 2018 ), have been documented to inhibit GSCs self-renewal ability.…”
Section: Introductionmentioning
confidence: 99%